2016
DOI: 10.1002/chem.201505052
|View full text |Cite
|
Sign up to set email alerts
|

Z‐Shaped Pyrrolo[3,2‐b]pyrroles and Their Transformation into π‐Expanded Indolo[3,2‐b]indoles

Abstract: Sterically hindered 1,4-dihydropyrrolo[3,2-b]pyrroles possessing ortho-(arylethynyl)phenyl substituents at positions-2 and -5 were efficiently synthesized through a sila-Sonogashira reaction. These unique Z-shaped dyes showed relatively strong fluorescence in solution. Detailed optimization revealed that, in the presence of InCl3, these alkynes readily undergo an intramolecular double cyclization to give hexacyclic products bearing an indolo[3,2-b]indole skeleton in remarkable yields. Steady-state UV-visible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…For these compounds, hypsochromic shifts in emission are also apparent ( λ ≈15–40 nm). Compounds 6 a – c emit blue‐to‐cyan light in dichloromethane ( λ max =461–498 nm).The absorption properties of dyes 5 a – c and 6 a – c are comparable with those of π‐extended indolo[3,2‐ b ]indoles and 7,14‐dihydrobenzo[ g ]benzo[6,7]indolo[3,2‐ b ]indoles . The angular fusion between the rings in all these classes of heterocycles results in absorption that spans over the UV spectral region and extends into the visible region to approximately λ =450 to 470 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these compounds, hypsochromic shifts in emission are also apparent ( λ ≈15–40 nm). Compounds 6 a – c emit blue‐to‐cyan light in dichloromethane ( λ max =461–498 nm).The absorption properties of dyes 5 a – c and 6 a – c are comparable with those of π‐extended indolo[3,2‐ b ]indoles and 7,14‐dihydrobenzo[ g ]benzo[6,7]indolo[3,2‐ b ]indoles . The angular fusion between the rings in all these classes of heterocycles results in absorption that spans over the UV spectral region and extends into the visible region to approximately λ =450 to 470 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The angular fusion between the rings in all these classes of heterocycles results in absorption that spans over the UV spectral region and extends into the visible region to approximately λ =450 to 470 nm. Unless strong electron‐withdrawing substituents are present, all of these compounds show emission maxima located at around λ =500 nm in CH 2 Cl 2 (DCM). The current study also shows that the introduction of a double‐helical motif combined with further π extension of compounds with a 1,4‐dihydropyrrolo[3,2‐ b ]pyrrole core induces dramatic decreases in the Φ fl value, as compared with previously obtained TAPPs and their π‐extended analogues .…”
Section: Resultsmentioning
confidence: 99%
“…For the Sonogashira coupling between 3 and 8 , or between 5 and 10 , Fu's catalytic system Pd(PhCN) 2 Cl 2 /P( t ‐Bu) 3 turned out to be necessary to attain regio‐selectivity and reasonable yields at room temperature (r.t.). InCl 3 ‐mediated alkyne benzannulation reaction turned out to be most efficient method for 12 and 14 among various known cyclization conditions . Interestingly, the cyclization went to the o ‐terphenyl units in 12 , while to the pyrene moiety in 14 , which is presumably due to different electron densities at the respective reactive sites.…”
Section: Methodsmentioning
confidence: 99%
“…The approximate arrangement of the aromatic and arylethynyl groups in 1 could be a potential motif that could be used to construct a highly fused polycyclic system via alkyne benzannulation reactions . Alkyne benzannulation reactions using a variety of Lewis/Brønsted acids and some electrophiles have been powerful strategies for the direct π‐extension of aromatic compounds . During the course of our study of phenanthrenes 1 , we found that the transannulation of 1 a upon two‐electron oxidation selectively afforded the azulene‐embedded PAH 2 a , which exhibited long‐wavelength absorption and amphoteric redox events originating from the non‐alternant characteristics of the embedded azulene core.…”
Section: Figurementioning
confidence: 99%